HERITAGE LANGUAGE EDUCATION IN ITALY: FIRST SURVEY AS PART OF A EUROPEAN PROJECT (ItalianoLinguadue, 2025)
The article presents the report of a European pilot project entitled Heritage language education in Europe: Legislative and educational challenges, promoted in 2022 within the 4EU+ Alliance. The article proposes some initial investigations on the Italian situation, considered both from the legislative point of view and from that of the practices implemented. Finally, an overview is proposed on the possibilities of continuing to learn hereditary languages in Italy, mentioning in particular the cases of Romanian, Chinese, Spanish, Arabic and Albanian. In conclusion, it emerged that the teaching of hereditary languages in Italy has very wide margins for implementation and improvement, and that although studies on the subject are well advanced and there are legislative indications, Italian language teaching practices do not appear to be completely up to date with the specificities of bilingual or foreign learners. L’educazione alle lingue ereditarie in Italia: prima indagine nell’ambito di un progetto europeoL’articolo presenta il report di un progetto pilota europeo intitolato Heritage language education in Europe: Legislative and educational challenges, promosso nel 2022 nell’ambito dell’Alleanza 4EU+. L’articolo propone alcune prime investigazioni sulla situazione italiana, considerata sia dal punto di vista legislativo sia da quello delle pratiche attuate. Viene infine proposta una panoramica sulle possibilità di proseguire l’apprendimento di lingue ereditarie in Italia, accennando in particolare ai casi del rumeno, del cinese, dello spagnolo, dell’arabo e dell’albanese. In conclusione è emerso come in Italia l’insegnamento delle lingue ereditarie presenti amplissimi margini di implementazione e di miglioramento, e come, sebbene gli studi sul tema presentino un buon stadio di avanzamento e le indicazioni legislative non manchino, le pratiche di insegnamento della lingua italiana non appaiano completamente aggiornate rispetto alle specificità che presentano gli apprendenti bilingui o stranieri.